Atypical Presentation of Thoracic Disc Herniation: Case Series and Review of the Literature. (4th April 2013) - Shirzadi, Ali; Drazin, Doniel; Jeswani, Sunil; Lovely, Leah; Liu, John
Abstract : Modern imaging has revealed that thoracic disc herniation (TDH) has a prevalence of 11–37% in asymptomatic patients. Pain, sensory disturbances, myelopathy, and lower extremity weakness are the most common presenting symptoms, but other atypical extraspinal complaints, such as gastrointestinal or cardiopulmonary discomfort, may be reported. Our objective is to make providers familiar with TDH's atypical symptoms to help avoid potential serious consequences created by a delay in diagnosis. We report the cases of two patients who each presented with atypical extraspinal symptoms secondary to a TDH. One patient presented with a chronic history of nausea, emesis, and chest tightness and MRI showed a large right paramedian disc herniation at T7-8. A second patient reported chronic constipation, buttock and leg burning pain, gait instability, and urinary frequency; an MRI of his thoracic spine demonstrated a central disc herniation at T10-11. TDH can present with vague extraspinal symptoms and unfamiliarity with these symptoms can lead to misdiagnosis with progression of the disease and unnecessary diagnostic tests and medical procedures. Therefore, TDH should be included in the differential diagnosis of patients with negative gastrointestinal, genitourinary, and cardiopulmonary system basic studies.